Hubungan Ekspresi Osteocalcin dan Interleukin-1β dengan Status Inflamasi Periodontal - Rahmavidyanti Priyanto; Malianawati Fauzia; Ariyati Retno Pratiwi; Neny Roeswahjuni; Novi Khila Firani (Fakultas Kedokteran Gigi Universitas Jember, 2022)
Periodontitis is inflammation of the periodontal tissue that can cause progressive damage to the periodontal ligament and alveolar bone. Clinical examination to determine the degree of damage to the alveolar bone using a periodontal probe instrument or probing. Cellular activity in the gingival crevicular fluid is thought to be a biomarker to determine the inflammatory status of the periodontal tissue. Cellular immune responses suggest the role of cytokines in the pathogenesis of gingivitis and periodontitis. The cytokines observed in this study were the protein Osteocalcin and Interleukin-1β (IL-1β) in the gingival crevicular fluid (GCF). In this study, 67 patients were examined for the condition of their periodontal tissues including the severity of gingivitis and periodontal probing. The gingivitis group was divided into 4 groups, namely normal, mild, moderate, and severe. Meanwhile, for probing samples were grouped based on probing into 3 groups. Group I (0-3 mm), group II (3.1-5 mm) and group III (> 5 mm). GCF was obtained using paper points that were left in the gingival sulcus for 30 seconds. Then paper points are put into cryovial tubes which are sent to the laboratory for ELISA test. The observed data on the expression of Osteocalcin and IL-1β were then performed statistical tests. Osteocalcin and IL-1β expression showed a significant difference with the severity of gingivitis cases. In the other hand, it did not show a significant difference with difference of periodontal pocket depth. Osteocalcin and IL-1β expression associated with the severity of gingivitis cases.